ASEAN Class Program di MTs. Muhammadiyah 1 Malang - Rijal, Najamuddin Khairur; Prasodjo, Haryo; Prinanda, Devita (Universitas Pendidikan Ganesha, 2020)
ThisÂ program is aimed to providing knowledge to students of MTs. Muhammadiyah 1 Malang about ASEAN and ASEAN Community. This is based on the lack of information for students about ASEAN because of the limitations of learning materials and information about ASEAN is only as a sub-subject. In addition, the school sees the importance of international insight to realize the vision of Elegant Morally, Excellent Intelectually. Therefore, through the ASEAN Class Program, there are activities such as the introduction of ASEAN and ASEAN community, sharing culture with Thai students, and sharing experiences and motivation with students who have international experience. The methods of activities include lectures, sharing, and discussion as well as pre-test and post-test. The result shows that there is an increased knowledge and understanding of participants about ASEAN and ASEAN Community and misinformation about ASEAN member countries and the ASEAN Community pillar can be corrected.